Implementasi Kebijakan Pengenaan Pajak Atas Penghasilan Youtuber Dalam Upaya Optimalisasi Penerimaan Pajak Di Kantor Pusat Direktorat Jenderal Pajak Tahun 2020 S.D 2022 - Wulandari, Winda; Yulianti, Fira (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The phenomenon of internet development has spread to all corners of the world including Indonesia and is growing rapidly along with the increasing number of internet users. In this case income from the internet, namely YouTube, has quite a big influence on state tax revenues. However, the imposition of taxes on YouTuber income is not yet optimal. So this research has the aim of knowing and analyzing the implementation of taxation policies on YouTuber income in an effort to optimize tax revenue. There are inhibiting and encouraging entities. This research method uses a qualitative type of descriptive approach. Data collection techniques were carried out by means of observation, interviews and documentation. The results of the study show that the imposition of tax on YouTuber income has not run optimally because there are no specific regulations regarding the imposition of YouTuber income tax. The inhibiting entities are the lack of continuous socialization, the difficulty of getting YouTuber data and the absence of collaboration with Google. The driving entities are optimizing socialization, working with third parties, the social network analytics system (SONETA), and the Account Representative (AR) approach